Rapid detection method of bacterial pathogens in surface waters and a new risk indicator for water pathogenic pollution - Min Gao; Feiyang Tan; Yuan Shen; Yao Peng (Scientific Reports, 2024)
Abstract In this study, a accurate, rapid quantitative PCR method for the simultaneous detection of 4 kinds of pathogenic bacteria in water was established, and the distribution of pathogenic bacteria in surface waters with different levels of pollution (Yulin region, China) was detected. The results showed that the detection accuracy was 94%; the detection limit was 2.7 in bacterial cells. Salmonella enterica subsp. enterica serovar typhimurium and Salmonella dysenteria were always present in water when the universal primer for pathogenic bacteria abundance detection was greater than 104 copies 100 mL−1. When the detection value is lower than 104 copy 100 mL−1, the bacteria in the water are rarely pathogenic bacteria, so the detection value of 104 copy 100 mL−1 can be used as a new indicator of waterborne pathogen pollution.